Effect of Operational Cost And Revenue On Return On Asset of SHARIA BANKNG : Case Study In Sharia Business Division of PT. Bank Sumut - Siti Mujiatun, S.E., M.M (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Effect of Operational Cost And Revenue On Return On Asset of SHARIA BANKNG : Case Study In Sharia Business Division of PT. Bank Sumut